Monitoring WWTP performance using size-exclusion chromatography with simultaneous UV and fluorescence detection to track recalcitrant wastewater fractions. (January 2019) - Ignatev, Alexey; Tuhkanen, Tuula
Abstract: A trial monitoring of a typical full-scale municipal WWTP in Central Finland was aimed to explore applicability of high performance liquid chromatography – size exclusion chromatography (HPSEC) with simultaneous UV and fluorescence detection as a tool for advanced routine monitoring of wastewater treatment. High, intermediate, and low molecular weight (MW) fractions of untreated wastewater (influent) and treated wastewater (secondary effluent) were characterized in terms of UV absorbance at 254 nm (UVA254 ) and specific fluorescence representing tyrosine-like, tryptophan-like, and humic/fulvic-like compounds. The activated sludge treatment removed 97 ± 1% of BOD, 93 ± 2% of COD, 71 ± 7% of DOC, and 24 ± 7% of TN, while the overall reduction of UVA254 was 50 ± 6%. Total fluorescence signal declined by ∼80% for tyrosine-like, by 60–70% for tryptophan-like, and by 7–36% for humic/fulvic-like compounds. Low and intermediate MW humic/fulvic-like compounds fluorescing at λ ex / λ em  = 390/500 nm demonstrated recalcitrant behavior. Protein-like and humic/fulvic-like fractions of low MW < 1 kDa accounted for 60–65% of total UVA254 and 50–70% of total fluorescence of whole influent and effluent samples. Strong linear correlations were observed between wastewater BOD, COD, DOC, UVA254 and tyrosine-like, tryptophan-like fluorescence. Graphical abstract: Image 1 Highlights: Low MW compounds in wastewater accounted for ∼60% of UVA254 and ∼70% of fluorescence. Conventional biological treatment reduced UVA254 by ∼50%. Total reduction of fluorescence followed the order: tyrosine-like > tryptophan-like > humic/fulvic-like. Linear correlations between BOD, COD, DOC, UVA254, and fluorescence were observed.